Structural, electrical and optical properties of metal complexes of NNS donor ligand - Biswas, Susobhan; Dagdelen, Fethi; Aydogdu, Yildirim; Dey, Kamalendu (Elsevier Science Sa, 2011)
The temperature dependence of electrical conductivity, optical property and crystal structure (PXRD) of [Ni(Hdammthiol)(CH3COO)] (1), [Co(Hdammthiol)(CH3COO)]center dot H2O (2) and [Cu(Hdammthiol)(CH3COO)]center dot H2O (3) [where H(2)dammthiol is the thiol form of the ligand diacetylmonoxime morpholine N-thiohydrazone (Hdammth)] complexes were investigated. The crystal structures of samples at room temperature were examined by using powder X-ray diffraction (PXRD). The results showed that all the complexes belong to the monoclinic system. Hot probe measurement indicated that these complexes had an n-type electrical conductivity. Optical absorption studies in the wavelength range 190-1100 nm at room temperature showed that the optical band gap E-gd of complexes 1-3 is 2.75 eV, 2.37 eV and 1.58 eV, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Inorganic compounds; Semiconductors; Electrical characterization; Powder diffraction